2014
DOI: 10.1155/2014/954508
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Platycodin D, a Saponin Purified from Platycodi Radix, on Collagen‐Induced DBA/1J Mouse Rheumatoid Arthritis

Abstract: The object of this study is to observe the effects of platycodin D, a saponin purified from Platycodi Radix, on mice collagen-induced arthritis (CIA). A daily dose of 200, 100, and 50 mg/kg platycodin D was administered orally to male DBA/1J mice for 40 days after initial collagen immunization. To ascertain the effects administering the collagen booster, CIA-related features (including body weight, poly-arthritis, knee and paw thickness, and paw weight increase) was measured from histopathological changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…Its monomers include Platycodin A, B, C, D, D2, D3, and Polygalacin D, D2 (Jin, 2007 ). According to some recent studies, Platycodin D showed bioactivity in anticancer (Chun et al, 2013 ), antirheumatoid arthritis and immunomodulatory (Kwon et al, 2014 ), and antiobesity (Lee et al, 2012 ). It was also reported that Platycodin D could regulate the production and secretion of airway mucin to prevent inflammatory diseases, which might explain the traditional use of Platycodon grandiflorum as expectorants in treating inflammatory pulmonary diseases (Ryu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its monomers include Platycodin A, B, C, D, D2, D3, and Polygalacin D, D2 (Jin, 2007 ). According to some recent studies, Platycodin D showed bioactivity in anticancer (Chun et al, 2013 ), antirheumatoid arthritis and immunomodulatory (Kwon et al, 2014 ), and antiobesity (Lee et al, 2012 ). It was also reported that Platycodin D could regulate the production and secretion of airway mucin to prevent inflammatory diseases, which might explain the traditional use of Platycodon grandiflorum as expectorants in treating inflammatory pulmonary diseases (Ryu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…It could relieve atopic dermatitis-like skin symptoms by suppressing NF-κ B and STAT1 and inhibiting TNF-α/IFN-γ-induced TARC expression (Choi et al, 2014 ). In addition, platycodin D could inhibit the production of IL-6 and TNF- α to cure rheumatoid arthritis (Kwon et al, 2014 ). Platycodin D was also spermicidal, contraceptive (Lu et al, 2013 ), and anti-atherosclerotic (Wu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The flavonoid hesperidin exerts marked antioxidant and antiarthritic activities in collagen-induced arthritis in rats: it lowers SF levels of the neutrophil marker elastase, nitric oxide, and lipid peroxidation; it mitigates depletion of reduced glutathione, superoxide dismutase, and catalase; it reduces paw erythema and edema and decreases cell infiltration, pannus formation, synovial hyperplasia, and bone resorption [ 142 ]. Similarly, the antiarthritic activity of Terminalia arjuna bark extract [ 136 ] and platycodin D [ 143 ] positively correlates with their antioxidant effect. Compared with untreated rats, T. arjuna extract reduces collagen-induced hind paw swelling, neutrophil infiltration, and articular elastase level (the biochemical marker of neutrophil infiltration).…”
Section: The Use Of Natural Products As Therapeutic Adjuvants To Tmentioning
confidence: 99%
“…Platycodin D, a saponin purified from Platycodi radix , exerts anti-inflammatory, antioxidant, and immunomodulating effects in collagen-induced arthritis in mice. This compound suppresses cytokine production in splenocytes and reduces joint swelling, the numbers of inflammatory cells infiltrated in the knee synovial cavity, and the paw levels of myeloperoxidase (a marker of neutrophil infiltration), oxidized lipids, IL-6, and TNF- α [ 143 ]. Together, these reports reinforce the hypothesis that modulation of free radical generation and chemical and biochemical pathways in activated neutrophils significantly contributes to reduce joint damage in arthritic animals.…”
Section: The Use Of Natural Products As Therapeutic Adjuvants To Tmentioning
confidence: 99%
“…), an anti‐rheumatoid arthritis effect (Kwon et al . ), cholesterol‐lowering effect and anti‐atherosclerotic activity (Zhao et al . ; Wu et al .…”
Section: Introductionmentioning
confidence: 99%